Effects of a visual literacy programme for the improvement of reading comprehension in primary and secondary school students. - Níkleva, Dimitrinka G.; Rodríguez-Muñoz, Francisco J. (L1-Educational Studies in Language and Literature, 2022)
With basis on previous research findings, a quasi-experimental longitudinal study was designed to analyse the effects of a visual literacy programme using images to improve reading comprehension. Pre-tests and post-tests were used for the recurring measurement of two homogeneous groups. The participants were 221 primary and secondary students in six schools within Andalusia and Madrid (Spain). The results indicated that visual literacy and, specifically, the reading and interpretation of connotative and symbolic images improve reading comprehension, especially at the global or macro-structural level, as well as literal and inferential reading, the comprehension of comparisons (similes) and metaphors, the ability to synthesize, and creativity. A moderate or large effect size was observed for all these variables. The effectiveness of the programme and the need for the planned, intentional use of images as pedagogical and didactic tools were confirmed.